Genetic analysis of stay‐green, yield, and agronomic traits in spring wheat. Issue 1 (1st November 2020) - Cook, J. P.; Acharya, R. K.; Martin, J. M.; Blake, N. K.; Khan, I. J.; Heo, H.‐Y.; Kephart, K. D.; Eckhoff, J.; Talbert, L. E.; Sherman, J. D.
Abstract: Hard red spring wheat ( Triticum aestivum L.) grown in rainfed environments in the northern Great Plains of North America frequently encounter drought and heat stress during grain‐fill, thus reducing yield. Delayed leaf senescence after heading, known as the stay‐green trait, has been found to help spring wheat tolerate drought and heat stress during grain‐fill. To better understand how the stay‐green trait relates to expression of other agronomic traits, data was analyzed from a recombinant inbred line (RIL) population derived from a 'Vida'/MTHW0202 cross grown in rainfed and irrigated environments. The genetic architecture controlling traits measured in this study were also examined. Results found the stay‐green trait was significantly correlated to overall yield ( P < .001, r = .37) in rain‐fed environments, but was not significantly correlated to yield ( P = .26, r = .09) in irrigated environments. Three quantitative trait loci (QTL) located on chromosomes 2D, 4A, and 4D were associated with the stay‐green trait. The 4A stay‐green QTL, previously designated QGfd.mst‐4A, was collocated with QTL for seed number per head, thousand kernel weight, and heading date. The 4D stay‐green QTL overlaps the Rht‐D1 plant height gene, and the allele prolonging the stay‐green period co‐segregates with the wild‐type (tall) Rht‐D1a allele. Results from this study provide a better understanding of the relationship between stay‐green and agronomic traits in rainfed vs. irrigated environments. Additionally, understanding the genetic architecture controlling stay‐green and agronomic traits will aid in selecting future drought‐tolerant spring wheat varieties. Core Ideas: Assessment of a wheat stay‐green trait for drought tolerance. Correlation of a stay‐green trait to grain yield and yield component traits. Genetic architecture of stay‐green and agronomic traits.